Studentsâ Rules and Practices: How to Speak English Fluently? - Desfitranita, Desfitranita (Institut Agama Islam Negeri Imam Bonjol Padang, 2017)
This study aims to investigate studentsâ rules and practices in how they maintain speaking fluency. Six students were the participants in this research that met the criteria. They were interviewed individually as the part of qualitative approach in research by using digital tape recorder. In-depth investigation was aimed at searching their rules and practices in maintaining fluency in speaking. The findings show that the participants skipped grammar rules but not the English tenses in speaking. Vocabulary learning starts from understanding words and phrases in context. Translation occurred when they met unfamiliar topic. Movie is mentioned as the perfect English language input. Last, the internet is the useful media to self-expose into rich English environments; it is easy and cheap to access. It is expected that the research contribute to the English language learning, speaking fluency in particular.